Metabolic Glycoengineering with N‐Acyl Side Chain Modified Mannosamines. Issue 33 (20th July 2016) - Wratil, Paul R.; Horstkorte, Rüdiger; Reutter, Werner
Abstract: In metabolic glycoengineering (MGE), cells or animals are treated with unnatural derivatives of monosaccharides. After entering the cytosol, these sugar analogues are metabolized and subsequently expressed on newly synthesized glycoconjugates. The feasibility of MGE was first discovered for sialylated glycans, by using N‐acyl‐modified mannosamines as precursor molecules for unnatural sialic acids. Prerequisite is the promiscuity of the enzymes of the Roseman–Warren biosynthetic pathway. These enzymes were shown to tolerate specific modifications of the N‐acyl side chain of mannosamine analogues, for example, elongation by one or more methylene groups (aliphatic modifications) or by insertion of reactive groups (bioorthogonal modifications). Unnatural sialic acids are incorporated into glycoconjugates of cells and organs. MGE has intriguing biological consequences for treated cells (aliphatic MGE) and offers the opportunity to visualize the topography and dynamics of sialylated glycans in vitro, ex vivo, and in vivo (bioorthogonal MGE). Abstract : Sugar for cells : Metabolic glycoengineering is a method to incorporate modified monosaccharides into cells, organs, or animals. Unnatural sialic acids can be generated by treatment with N ‐acyl side chain modified mannosamines. The application of this technique has intriguing biological consequences for treated cells. Mannosamine analogues bearing reactive groups can be used, for example, to visualize sialylated glycoconjugates.